PENGARUH FINANCIAL LITERACY DAN GAYA HEDONISME TERHADAP FINANCIAL BEHAVIOR DENGAN FINTECH SEBAGAI MODERASI PADA MAHASISWA S1 AKUNTANSI UNIVERSITAS WIJAYA KUSUMA SURABAYA - Della Nur Octavia; Sarah Yuliarini (Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the influence of financial literacy and hedonistic lifestyle on students' financial behavior, as well as the role of financial technology as a moderating variable in this relationship. The research was conducted using a quantitative method. The type of data used in this study is primary data collected through the distribution of questionnaires to 153 active students of the Accounting undergraduate program at Wijaya Kusuma University Surabaya. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 4 software. The results of the study indicate that financial literacy has a positive effect on financial behavior, while a hedonistic lifestyle has a negative effect. Fintech has been proven to moderate both relationships, strengthening the positive relationship between financial literacy and financial behavior as well as enhancing the negative impact of a hedonistic lifestyle on financial behavior.